2022
DOI: 10.3389/fonc.2022.746643
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Promoter Hypomethylation Acts As a Diagnostic Biomarker in Hepatitis B Virus-Associated Hepatocellular Carcinoma

Abstract: BackgroundNew biomarkers are needed to detect hepatocellular carcinoma at an earlier stage and to individualize treatment strategies. IL-6 has been proven to be associated with liver cancer in numerous studies.AimTo evaluate the value of the IL-6 promoter methylation level as a noninvasive biomarker for the diagnosis of liver cancer.MethodsA retrospective analysis of 165 patients with HBV-associated hepatocellular carcinoma (HCC), 198 patients with chronic hepatitis B (CHB) and 31 healthy controls were involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In conclusion, the study revealed that in HBV-associated HCC, the methylation levels of the IL-6 promoter were notably lower than those observed in patients with chronic hepatitis B. Conversely, the IL-6 mRNA levels were significantly elevated in HBV-associated HCC compared to both CHB patients and healthy individuals [63].…”
Section: Hcc-new Pieces To the Puzzlementioning
confidence: 60%
See 1 more Smart Citation
“…In conclusion, the study revealed that in HBV-associated HCC, the methylation levels of the IL-6 promoter were notably lower than those observed in patients with chronic hepatitis B. Conversely, the IL-6 mRNA levels were significantly elevated in HBV-associated HCC compared to both CHB patients and healthy individuals [63].…”
Section: Hcc-new Pieces To the Puzzlementioning
confidence: 60%
“…The study involved 165 patients diagnosed with HCC associated with hepatitis B virus, 198 patients with chronic hepatitis B, and 31 healthy individuals serving as controls. The research employed Methylight methodology to detect methylation levels in the IL-6 promoter region within peripheral blood mononuclear cells (PBMCs) [63].…”
Section: Hcc-new Pieces To the Puzzlementioning
confidence: 99%
“…Hepatocellular carcinoma (HCC), a common malignancy, is one of the dominant causes of cancer-associated deaths worldwide ( Khemlina, Ikeda & Kurzrock, 2017 ). It has been reported that HCC accounts for approximately 90% of liver cancer, with a prevalence rate of 4.7% of all tumors and a mortality rate of 8.3% worldwide ( Yang et al, 2022 ). Currently, surgical resection, transplantation, and ablation are the standard therapeutic strategies for early-stage HCC ( Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%